Diversity, habitat associations and stock structure of odontocete cetaceans in the waters of American Samoa, 2003-06 - Johnston , David W.; Robbins , Jooke; Chapla , Marie E.; Mattila , David K.; Andrews , Kimberly R. (J. Cetacean Res. Manage., 2023)
Little is known about the species composition, distribution, abundance or stock structure of odontocetes in the central and western tropical Pacific Ocean, including those inhabiting the US Exclusive Economic Zone (EEZ) waters of American Samoa. While some information on species presence in this region has been gleaned from anecdotal sightings and whaling and stranding records, odontocete diversity in the waters of American Samoa has never been formally investigated. This lack of information precludes efforts to determine the sustainability of cetacean populations within US EEZ waters. This paper reports on the first dedicated surveys to document the presence and distribution of odontocete cetaceans in the waters of American Samoa. A series of small-boat photo-identification and biopsy surveys for cetaceans were conducted in the nearshore waters of Tutuila during 2003-06. In addition, ship-based visual surveys were conducted in the waters surrounding the Manu‘a Islands, Rose Atoll and Swains Island in summer 2006. A total of 58 groups of odontocete cetaceans were encountered during both small-boat and ship-based surveys: spinner dolphins (Stenella longirostris, n=34), rough-toothed dolphins (Steno bredanensis, n=10), sperm whales (Physeter macrocephalus, n=3), false killer whales (Pseudorca crassidens, n=5), bottlenose dolphins (Tursiops truncatus., n=1), dwarf sperm whales (Kogia sima, n=1), short-finned pilot whales (Globicephala macrorhynchus, n=1), and three groups of unidentified odontocetes. Photographs were analysed for quality and individuals with distinctive markings were selected for entry into a photo-identification catalogue. The resultant catalogue included 46 spinner dolphins, 41 rough-toothed dolphins, 2 bottlenose dolphins, 5 false killer whales, 4 pilot whales, 1 dwarf sperm whale and 4 sperm whales. Thirteen spinner dolphins and 14 rough-toothed dolphins were sighted in multiple years. To investigate stock structure, spinner dolphin genetic data were used to compare mitochondrial control region genetic diversity and allele frequencies between American Samoa and the Hawaiian Islands. American Samoa had a higher genetic diversity, and populations at the two locations were genetically distinct (FST = 0.21). The high diversity at American Samoa indicates that spinner dolphins at this location are not reproductively isolated, but the data do not rule out the possibility that these dolphins may be demographically isolated on ecological timescales.